Quality Approach In The Development Of Management Information System In Higher Education - Fory Armin Naway; Arifin Suking; Ikhfan Haris; Abdul Rahmat (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
Management Information Systems (MIS) is a data processing procedure based on the information technology as a tool to produce the information in a timely and effective way to support the management in decision making process. In developing a management information system, quality approach has become essential factor due to the function of quality control in assuring the performance of the organization activities. Establishing of Management Information Systems at the higher education institution driven by many reason, such as: (1) Management Information Systems is designed to support the operations, management, and decision functions of an organization, (2) Management Information Systems enable the organizations planning, control, and operational functions to be carried out effectively and the means of efficient coordination between Departments; quick and reliable referencing (3) Management Information System could be a tool by striving toÂ highest quality standards in the teaching and learning process, (4) Management Information Systems provides a valuable time-saving benefit to the workforce in term of quick and reliable referencing; access to relevant data and documents; use of less labor; improvement in organizational and departmental techniques; management of day-to-day activities and (5) Management Information Systems can effectively respond to the changing of society demands in their interest in dependable and reliable information as well as easily.